برهنة وجود الله وتفنيد النظرية الداروينية من منظور النورسي - Muhammad Soleh, Amad Kazim; `Abdullah, Mustaffa (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
This study briefly shows a reformist thoughts of Badi` al-Zaman al-Nursi, as well as his role in proving the truth of faith as there must be a God, with comprehensive methodological arguments consisting of Quranic methodology, scientific evidence, philosophical and logical arguments, and refute philosophy of materialism and Darwinism such as theory of evolution and the theory of natural selection. This study also try to negate it by using a philosophical approach against defective thought and replace it with other methodologies which compatible with spirit of the Quranic revelation and suit with the requirements of the conflict between Islam and its rivals.